Adolph Rupp and the rise of college basketball - Bolin, James Duane, 1955- (The University Press of Kentucky, 2019)
"As the person most responsible for creating the phenomenon that is University of Kentucky basketball, Adolph Rupp (1901-1977) is a legend in Kentucky and in the larger world of Division I college basketball. As UK's coach from 1930-1972, Rupp led the program to four NCAA championships and is the third most winning coach in NCAA history, behind Bobby Knight and Dean Smith. Rupp's record is not without blemish, however. In the late 1940s, three of his players were indicted in a point-shaving scandal, and in more recent years his legacy has been tarnished by claims that he was a racist. He was portrayed as such in the 2006 film Glory Road, which dramatized the 1966 defeat of the popular (and all-white) Rupp's Runts to an all-black Texas Western team in the NCAA championship game. In Adolph Rupp and the Rise of Big-Time College Basketball in America, James Duane Bolin sets the record straight by presenting a balanced picture of Rupp, with all of his faults-and incredible successes-firmly intact. Drawing upon a wealth of primary sources--including game summaries, correspondence, business and legal records, and hundreds of hours of recorded interviews with Rupp's relatives, former players, assistant coaches and administrators, and even the man himself--Bolin is able to provide an unprecedented level of insight into Rupp's life. The book begins with Rupp's youth in Kansas, including accounts of his interactions with James Naismith, basketball's inventor. Subsequent chapters examine his professional life, both before and during his tenure at UK; his most storied teams, including the Fabulous Five, which won championships in 1948 and 1949; and his many other business interests, such as his 500-acre farm and bourbon distilling"--